PARTICIPATORY DISASTER RISK MAPPING FOR TOURISM INDUSTRY REGION - Amiruddin, Lutfi; Rozalinna, Genta Mahardhika (Wisesa: Jurnal Pengabdian Masyarakat, 2023)
In order to increase knowledge of disaster risk reduction, we invited some representatives of residents in the tourism industry region to create disaster maps in a participatory approach. This activity conducted according to the points of the Sendai Framework on Disaster Risk Reduction (DRR) using local knowledge in creating disaster information. The information in our disaster maps were gathered from Focus Group Discussions (FGD), which explored community knowledge related to hazards, vulnerabilities, and disaster risks. Subsequently, the data were visualized through a participatory disaster map that illustrates local knowledge of participants. However, the map of the pandemic disaster cannot yet be described due to the emergence of conflict among residents regarding the implementation of Large-Scale Social Restrictions (PSBB) and several other schemes, which have an impact on tourism. Ultimately, through the making of a participatory disaster risk map, we hoped that disaster mitigation can be initiated independently from local people.